Prevalence and risk factors of low back pain - Ramdas, Jella; Jella, Vasantha (International Journal of Advances in Medicine, 2018)
Background: Low back pain is one of the most common health problems among all the population of the world. Men and women are equally reported to be affected by this condition. Of late, there has been rising incidence of LBP among many young adults and children, which is of concern. There have been a few studies regarding LBP but very few in this part of the world. This study was hence conducted to assess the prevalence of lower back pain among the young adults in our area. Methods: Detailed demographic picture was taken from all the patients which included the age, gender, smoking and alcoholic status, socio economic status, travelling, type of work, hours at work. Type and duration of sport, history of previous LBP, the intensity of pain, way it is relieved, duration of pain, i.e. the frequency of pain in a day are also taken into account. Results: The most common age group to be affected among the males was 31-40 years of age, where 38.6% were affected, while amongst the female the most common age group to be affected was 41-50 years with 38.1%. Most of the patients has strenuous physical exercise on daily basis for long period of time (70.9%). 58.3% patients were under stress and anxiety, while 56.3% lifted heavy weights regularly. 44.7% persons were either overweight or obese and had LBP due to the excess weight, while 28.6% had LBP due to sitting for long periods. Conclusions: This study shows that lower back pain is prevalent among all the age groups, especially among the younger adults. Identification of predisposing factors among the individuals which cause LBP can lead to diagnosing the condition at the earliest and preventing chronic pain, thereby improving the quality of life.